Tree Ring–Based Drought and Flood Analyses from the Himalayan Region Limitations, Challenges, and Future Perspectives - Shekhar, Mayank; Singh, Ayushi; Chinthala, Bency David; Tomar, Nidhi; Roy, Ipsita; Ranhotra, Parminder S.; Bhattacharyya, A. (CRC Press, 2023)
This chapter provides information about the past climate, drought, and flood occurrences in the Himalayan region on a long-term perspective based on dendrochronological (tree-ring) data. Evaluation of the published tree-ring records of past climate, drought, streamflow, and flood reconstructions from the Himalayan region put forth that a good number of tree and shrub species have distinct annual growth rings that make them suitable for dendrochronology and its varied applications. In general, the conifers, mainly Cedrus deodara (Roxb.) G. Don and species of Pinus growing in the Himalayan region are reported to have excellent potential to reconstruct long records of past climate for the Indian subcontinent. For the purpose of dendrochronological applications, the reconstruction of temperature, drought, and streamflow ate to the 5th to 7th century, whereas the recently attempted reconstruction of flooding events covers the 20th century (i.e., since 1900). The available tree ring–based past hydroclimate records thus provide an overview of the past drought and pluvial episodes for the Himalayan region. Such a database would improve understanding of the hydroclimatic behavior in various subregions of the Himalayas that would help in developing suitable adaptive measures for mitigation and robust models for a long-term perspective. Challenges, however, remain toward the availability of long records and poor spatial distribution that limits the proper understanding of hydroclimate behavior over the entire Himalayan region and its global teleconnection.
CRIS-Team Scopus Importer:2023-09-15